1991
DOI: 10.1111/j.2042-7158.1991.tb03471.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal absorption of quaternary ammonium compounds correlated to their binding to small intestinal brush border membrane in rat

Abstract: The relationship between absorption of quaternary ammonium compounds (QACs) from rat intestine and their in-vitro binding to isolated brush-border membrane has been examined, using a series of n-alkyltrimethylammoniums. The binding of these QACs gradually increased with each extension of unbranched hydrocarbon chain from octyltrimethylammonium to tetradecyltrimethylammonium. However, hexyltrimethylammonium and heptyltrimethylammonium failed to bind to the membrane. On the other hand, the disappearance of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The absorption in the two species is affected by gastrointestinal transit, luminal contents and membrane permeability, and one or several factors may cause the differences. In general, Saitoh [23] suggested that the size of the hydrophobic part of a quaternary ammonium compound was a principal determinant of both absorption and membrane binding. But the absorption process for quaternary ammonium ions is much more complicated.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption in the two species is affected by gastrointestinal transit, luminal contents and membrane permeability, and one or several factors may cause the differences. In general, Saitoh [23] suggested that the size of the hydrophobic part of a quaternary ammonium compound was a principal determinant of both absorption and membrane binding. But the absorption process for quaternary ammonium ions is much more complicated.…”
Section: Discussionmentioning
confidence: 99%